The Typology and Functions of Fawātiḥ al-Suwar within the Structural Framework of the Qur’an - Nurussyifa, Adinda Aisyah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses Fawātiḥ al-Suwar within the context of Qur’anic exegesis (tafsīr) and ʿUlūm al-Qur’ān from a linguistic perspective, focusing on their structural functions and variations throughout the Qur’anic system. The method employed in this research is library research, which involves collecting information and data from various sources available in libraries such as documents, books, journals, historical records, and other relevant materials. The primary sources used in this study are derived from several classical works on ʿUlūm al-Qur’ān that are relevant to the topic. The approach adopted in this article is qualitative and descriptive. The findings indicate that Fawātiḥ al-Suwar represent one of the unique and miraculous features of the Qur’an’s composition, reflecting the profound meaning and divine eloquence (balāghah ilāhiyyah) of its expression. Prominent exegetes such as al-Qurṭubī, al-Rāzī, and Ibn ʿĀshūr explain that the openings of the Qur’anic chapters possess their own secrets, containing spiritual, rhetorical, and thematic messages. The fawātiḥ serve as an introduction to the meanings and as an affirmation of each surah’s central theme. Among their forms, ten main types can be identified: openings with praise, openings with al-ḥurūf al-muqattaʿah (disjointed letters), openings with vocatives (nidāʾ), openings with declarative statements (jumlah khabariyyah), openings with oaths (qasam), openings with conditional particles (ḥurūf sharṭ), openings with imperative verbs (fiʿl amr), openings with interrogatives (istifhām), openings with supplications (duʿāʾ), and openings with causal statements (taʿlīl).